Estimation of a modern stage of wind resources in the Ukrainian Carpathians and their changes regarding the base climatological period - Osadchy, V. I.; Skrynyk, O. A.; Skrynyk, O. Y. (Reports of the National Academy of Sciences of Ukraine, 2015)
Basing on empirical data, we have estimated the modern stage (during 1981–2010) of wind resources in the Ukrainian Carpathians. Detailed (with high spatial resolution) maps of wind potential capacity at different heights are constructed. Comparative analysis of the results against analogous results for 1961–1990 shows a considerable decrease of wind resources in 1981–2010. Statistical significance of the revealed changes is justified.